Extraction and characterization of essential oil from ginger (Zingiber Officinale Roscoe) and lemongrass (Cymbopogon Citratus) by microwave-assisted hydrodistillation (MAHD) - Ranitha, Mathialagan (2012)
Microwave-assisted hydrodistillation (MAHD),an advanced distillation method that take advantage of microwave heating with the conventional hydrodistillation,recently been widely attended for the extraction of essential oil from medicinal plants and herbs due to its economic and green technology. One way in maximizing the efficiency of a method is optimizing its parameter condition to obtain maximum yield. In that case,this study was carried out to investigate the performance of MAHD in the extraction of essential oil from Ginger (Zingiber Officinale Roscoe) and Lemongrass (Cymbopogon citratus).The effect of three main factors which were microwave power,extraction time and water to raw material ratio were investigated to optimize the extraction operating conditions for obtaining maximum oil yield.As a result the best condition that has been determined for maximum essential oil production were under 250 W microwave power for 90 minutes at water to raw material ratio of 8:1. This optimum condition was finalized based on its maximum yield from Ginger (Zingiber Officinale Roscoe) and Lemongrass (Cymbopogon citratus) which were 0.85% (w/w) and 1.37%(w/w),respectively.Then,the oil samples at different extraction time were analyzed to evaluate its quality by determined its chemical constituent through GC-MS.The main components detected in the essential oil of Ginger (Zingiber Officinale Roscoe) were Borneol,β-Bisabolene,Cineole,α-Cedrene,α-Curcumene,β-Farnesene(E),β-Sesquihelladiene,β-Thujene and Zingiberene. Wherelse, the main components in the essential oil of Lemongrass (Cymbopogon citratus) were Citral,Geranic Acid,Geranyl Acetate,Linalool, Neric acid, (Z) Citral,β-mycrene and β-Thujene.The dominant component in the essential oil of Ginger (Zingiber Officinale Roscoe) and Lemongrass (Cymbopogon citratus) were Zingiberene and Citral, respectively.The maximum oil yield from Ginger (Zingiber Officinale Roscoe)and Lemongrass (Cymbopogon citratus) were obtained at shorter extraction period without significant affect on their chemical constituents.This may prove MAHD as a cost effective method and also expected would bring volume of worth in the essential oil production industry.